2008
DOI: 10.1097/meg.0b013e3282f16a8c
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus transmission among oral crack users: viral detection on crack paraphernalia

Abstract: HCV transmission from an infected host onto paraphernalia as a precondition of HCV host-to-host transmission via shared crack paraphernalia use seems possible, with oral sores and paraphernalia condition constituting possible risk modifiers. Larger-scale studies with crack users are needed to corroborate our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 16 publications
3
48
0
8
Order By: Relevance
“…Based on the evidence for distinct injury/morbidity risks associated with crack use (Faruque et al, 1996;Fischer, Powis, Firestone Cruz, Rudzinski, & Rehm, 2008;Haydon & Fischer, 2005;Porter, Bonilla, & Drucker, 1997), 'safer crack use paraphernalia' (SCUP) distribution initiatives have been implemented in select locales as targeted efforts to reduce such risk outcomes. SCUP programs are typically offered as community-based outreach initiatives, distributing simple 'kits' of basic materials (e.g., break-safe glass stems, rubber mouthpieces, metal screens for safer crack pipe assembly; (Haydon & Fischer, 2005;Malchy, Bungay, Johnson, & Buxton, 2011) -plus basic information and health promotion elements -to facilitate safer crack use practices.…”
Section: Material/environmental Interventions: Drug Consumption Facilmentioning
confidence: 99%
“…Based on the evidence for distinct injury/morbidity risks associated with crack use (Faruque et al, 1996;Fischer, Powis, Firestone Cruz, Rudzinski, & Rehm, 2008;Haydon & Fischer, 2005;Porter, Bonilla, & Drucker, 1997), 'safer crack use paraphernalia' (SCUP) distribution initiatives have been implemented in select locales as targeted efforts to reduce such risk outcomes. SCUP programs are typically offered as community-based outreach initiatives, distributing simple 'kits' of basic materials (e.g., break-safe glass stems, rubber mouthpieces, metal screens for safer crack pipe assembly; (Haydon & Fischer, 2005;Malchy, Bungay, Johnson, & Buxton, 2011) -plus basic information and health promotion elements -to facilitate safer crack use practices.…”
Section: Material/environmental Interventions: Drug Consumption Facilmentioning
confidence: 99%
“…These high HCV infection rates among non-injection crack users have given rise to the hypothesis that HCV transmission among crack users might occur through the sharing of HCV-contaminated oral crack-use paraphernalia (Faruque et al, 1996;Roy et al, 2004;Tortu, McMahon, Pouget, & Hamid, 2004). One recent study suggested that on the basis of virological detection of HCV on crack paraphernalia that such transmission between crack users might be plausible (Fischer et al, 2008b). Besides physical health problems, crack users also feature disproportionately elevated levels of mental health problems, for example, antisocial personality disorders, paranoia and depression.…”
Section: Introductionmentioning
confidence: 96%
“…8 Among this population, using or sharing improper inhalation equipment (whether for financial, social or relational reasons) is a key modifiable behaviour associated with increased transmission of infectious diseases. 9 Harm-reduction programs provide clean inhalation equipment (e.g., glass stems, mouthpieces, push sticks and brass screens) in an effort to reduce the harms associated with using ill-devised paraphernalia and sharing. 8 Initial evaluations have shown associations between programs providing appropriately built crack pipes and reduced sharing, reduced crime and violence to obtain pipes, and reduced sourcing of pipes from the street, as well as transactional sex to obtain pipes.…”
Section: What Investigations Should Be Arranged?mentioning
confidence: 99%